Yield, chemical composition and persistence of alfalfa on moderately acidic mountain soil - Josip Leto; Mladen Knežević; Krešimir Bošnjak; Marina Vranić; Goran Perčulija; Ivana Matić; Hrvoje Kutnjak; Žarko Miljanić (Mljekarstvo)
Due to its excellent nutritional characteristics and high yields, alfalfa is the most important forage crop in roughage production. The main limiting factor in global food production is soil acidification. At the moment, about 40% of world agricultural soils are acidic. It is difficult to grow alfalfa on acid soils (pH <5.2), trough it is recently spreading also on soils with pH value 5.2-6.2. Almost 50% of the Republic of Croatia territory is situated in hilly and mountainous regions. Since soils in these regions are often of acid reaction, alfalfa production on such soils can be ensured by appropriate agroameliorative and agrotechnical practices, as well as by choosing more tolerant (plastic) cultivars, selected for production on acidic soils. The objective of this research was to explore the possibility of growing different imported alfalfa cultivars on moderately acidic mountain soil. In all three investigated years there were no significant differences between cultivars in dry matter (DM) yield within particular cuttings as well as in total annual DM production (P>0.05). Average DM yield of all cultivars in the year 2000 was 7.07 t/ha, in the year 2001 it was 10.94 t/ha, and finally in the year 2002 it was 12.78 t/ha. Significant differences in DM yields were recorded between cuttings (P<0.01) in all experimental years. There were no significant differences between cultivars in all chemical parameters (P>0.05). Mean crude protein content was 28.2%, while contents of crude fat, crude fibers and non nitrogen free extract (NFE) were 3.73%, 16.15%, 29.19%, respectively. No significant differences in alfalfa ground cover were recorded between cultivars in autumn or in spring in all experimental years (P>0.05). Significant differences in alfalfa ground cover in autumn (P<0.05) and in spring (P<0.01) were recorded between years. The lowest average ground cover was recorded in last experimental year: in the autumn of the year 2001(72.81%) and in the spring of the year 2002 (64.37%). All investigated alfalfa cultivars are suitable for growing in similar agroecological conditions.